Hubungan antara Kebersyukuran dan Subjective Well-Being pada Perawat Wanita dan Bidan di RSU Sis Al-Djufrie Palu - Muhammad Shodikul Haq; Ahmad Muhammad Diponegoro; P Purwadi (Psyche 165 Journal, 2021)
This research aims to determine the relationship between Gratefulness and Subjective Well-Being. The research subjects used in this research were 34 female nurses and midwives at Sis Al-Djufrie Hospital, Palu City. This research uses quantitative methods. Data obtained instrument from a scale to measure Gratitude questionnaire to see the life-size of the subject and the Positive affect negative affect schedule-Expanded form scale to measure positive and negative effects on individuals and use the Satisfaction with Life Scale to measure the level of individual life satisfaction. Analysis of the data used is using Pearson Product Moment correlation. The result of data analysis showed a correlation coefficient of 0.655 with a significance of 0.000 (p <0.05) and showed a very significant positive relationship between thanksgiving and Subjective Well-Being. The results of this study indicate that the contribution given by gratitude to the Subjective Well-Being is 42.9 percent, this indicates a very significant relationship between the variables of Gratitude and Subjective Well-Being towards female nurses and midwives.